The Effectiveness of Blended Learning with Discovery Learning Model on Buffer Solution Materials to Improve Science Process Skills - Dicky Saputra; Ila Rosilawati; Gamila Nuri Utami (Universitas Lampung, 2022)
This study aims to describe the effectiveness of discovery learning model on buffer solution materials to improve students’ science process skills. This research is a quasi-experimental study with the matching-only pretest and posttest control group design.Population on this study is all students of class XI IPA of SMAN 1 Sukadana EastLampung in even semester of the 2021/2022 academic year. The sampling techniqueused purposive sampling and obtain class XI IPA 3 and class XI IPA 2 as experimental class and control class, respectively. Hypothesis testing used the analysis of the average post-test value calculation using the difference test of two average by t-test. The results showed that: (1) the average post-test scores of students’ science process skills in the experimental class were significantly different from post-test scores in the control class which is high-categorized of 0,71. Thus, it can be concluded that blended learning with discovery learning model is effective to improve students’ science process skills. Keywords: discovery learning, blended learning, buffer solution, science process skills.